(untitled) (Journal of the College of Basic Education, 2022)
Samples are made with dimensions of 20 mm in diameter and 3 mm in height were manufactured from 316L steel plate, as the samples were prepared by the method of thermal spraying with flame, different percentages of Ni-Al and (0,5,10,15,20,25) % were taken. The base material of silica SiO2, thus forming cermet samples (ceramic + metal). The samples were sintered at a temperature of 900°C for two hours, and physical and mechanical tests were conducted, which obtained the best results at the optimal values ​​from a spray distance of 16 cm, and sintering 900 °C, and the mixing ratio is 25%, and it was found that the hardness was (590Hv), while the lowest porosity was (4.5%), and the highest adhesion strength was (38MPa), while the lowest value for wear was (0.11), while the structural results were represented by examination of the microscope Scanning Electron (SEM) has shown that the best models of entanglement homogeneity are 25% of the Ni-Al reinforced metallic material